Molecular Detection of Monilinia fructigena as Causal Agent of Brown Rot on Quince - Hrustić, Jovana; Grahovac, Mila; Mihajlović, Milica; Delibašić, Goran; Ivanović, Mirko; Nikolić, Mihailo; Tanović, Brankica (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2012)
Species of the genus Monilinia are important causal agents of fruit rot on pome and stone fruits in Serbia. The pathogen is very harmful, especially on small properties and cottage plantations where intensive control measures are not applied. Quince is important host for the pathogens of this genus. During spring 2010, intensive occurrence of mummified fruits overwintering on branches of the quince was observed. The pathogen was isolated using standard phytopathological methods. Pathogenicity of eight obtained isolates was tested by artificial inoculation of injured apple fruits. Identification was performed according to pathogenic, morphological and ecological properties, and was confirmed by Multiplex polimeraze chain reaction, PCR. All the isolates studied caused brown rot on inoculated apple fruits. The isolates form light yellow colonies with lobate margins, with single-celled, transparent, elliptical or oval conidia in chains, regardless temperature or light presence. Sclerotia are observed in 14 days old cultures. The highest growth rate of most of the isolates is at 27°C and in dark. Based on studied pathogenic, morphological and ecological characteristics, it was found that the Monilinia fructigena is causal agent of brown rot of quince. Using specific primers (MO368-5, MO368-8R, MO368-10R, Laxa-R2) for detection of Monilinia species in Multiplex PCR reaction, the expected fragment 402 bp in size was amplified, which confirmed that the studied isolates belonged to the species M. fructigena.